Apheresis Procedure could Prevent Sequele of Hsv1 Encephalitis-Case Report - Vjeroslava Slavic (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2020)
Background: Herpes simplex virus 1 is consistently the most common cause of sporadic encephalitis worldwide which leaves neurological deficits in more than 60% of survived patients. The immune response of a diseased person has a major impact not only on the course of the disease, but also on the response to the applied protocol, as well as the severity of brain damage. The proposed immunomodulatory therapy aims to restore the quality of the immune system, both innate and acquired to improve outcome of encephalitis. Case report: Here we present case report of encephalitis treated according to the guidelines, who developed severe brain damage with consequent memory and cognition deficits as well as language disorders. In order to mitigate brain damage, our patient started apheresis protocol consisting of four sessions based on nanomembrane with four sessions of extracorporeal Laser blood irradiation, by red and infrared beams. Apheresis protocol was conducted in P. Pavlov First St. Petersburg State Medical University, Russia, on Hemophoenix device as minimally invasive and safe (plasma replacement with saline solution). The effect was such that the patient returned to full-time work five months after onset of encephalitis. MRI brain scan within six months after apheresis showed signs of good regression, but one year later defects was in good remission. Conclusion: Apheresis procedure based on nanomembrane consist of four sessions, every other day, with extracorporeal Laser blood irradiation could mitigate sequelae of brain damage caused by herpes simplex virus 1 encephalitis.